Gravity‐Derived Antarctic Crustal Thickness Based on the Gauss‐FFT Method. (26th August 2022) - Ji, Fei; Wu, Leyuan; Zhang, Qiao
Abstract: The information on crustal thickness in Antarctica can provide significant constraints on its crustal deformation and tectonic evolution. To generate reliable images of crustal features, we investigate the model of Moho depth and crustal thickness beneath Antarctica by applying the Bott‐Parker's formulas based on the Gauss‐fast Fourier transform method through a comprehensive analysis of gravity data, ice and sediment thicknesses and bedrock elevation, combined with seismic constraints. Tests with synthetic data indicate that the iterative inversion algorithm can yield a highly accurate Moho topography. Ultimately, inverted crustal thickness reveals a more detailed crustal image by clearly identifying more tectonic elements at different scales than previous results and correlates well with major tectonic provinces. Airy isostasy and flexural isostasy models are used to assess the crustal isostatic compensation. The distinctive negative isostatic anomalies are observed in the Transantarctic Mountains and the East Antarctic areas of the great escarpment in the Dronning Maud Land and Aurora and Wilkes Subglacial Basin, indicating that the low density of the uppermost mantle and lithospheric strength may play important roles in compensating for their elevations. Variations in crustal thickness in interior East Antarctica are analyzed; the thickened crust from Dronning Maud Land to the Gamburtsev Subglacial Mountains may be associated with the collision of continental blocks and is interpreted as the fossil sutures. We compare the relationship between the Moho and Curie interfaces and find that the uppermost mantle is magnetized in some areas of East Antarctica, which may indicate preserved Precambrian cratonic roots. Plain Language Summary: Crustal thickness is an important parameter for understanding the Antarctic crustal structure. However, due to the harsh polar conditions, most of the Antarctic crustal configuration is concealed. In this study, an iterative method to analyze gravity and seismic data is used to invert high resolution model of Moho depth and crustal thickness over Antarctica. Our results reveal large heterogeneity in crustal thickness: thick East Antarctica, strongly thinned West Antarctica and dramatic variations along the axis of the Transantarctic Mountains. A comparison of inverted Moho depth in this study against recent published models shows a good agreement, but our model can reveal more structural details. The joint analysis based on Airy and flexural isostatic model suggest that the Antarctic topography is supported by various sources. We find the magnetic remanence in the uppermost mantle beneath the western Ross Ice Shelf and the center and marginal regions of East Antarctica, which reflects transformation of rock and a cold lithosphere, respectively. These results can shed light on the crustal deformation and geological history of Antarctica. Key Points: We present a new model of Antarctic crustal thickness by combining Parker's forward algorithm and Bott's iterative inversion technique Comparison of Moho and Curie depths tells that the uppermost mantle is magnetized in parts of East Antarctica representing ancient cratons The thickened crust in East Antarctica is the result of the collision of continental blocks and is interpreted as the possible sutures